Physiognomy and the meaning of expression in nineteenth-century culture - Hartley, Lucy (Cambridge studies in nineteenth-century literature and culture, 2001)
In Physiognomy and the Meaning of Expression in Nineteenth-Century Culture, Lucy Hartley examines the emergence of physiognomy as a form of popular science. Physiognomy posited an understanding of the inner meaning of human character from observations of physical appearances, usually facial expressions. Taking the physiognomical teachings of Johann Caspar Lavater as a starting-point, Hartley considers the extent to which attempts to read the mind and judge the character through expression can provide descriptions of human nature.